2013
DOI: 10.1111/eth.12104
|View full text |Cite
|
Sign up to set email alerts
|

Is the Soft Song of the Brownish‐Flanked Bush Warbler an Aggressive Signal?

Abstract: Soft songs have been detected in many songbirds, but in most species, research on soft songs has lagged behind studies of broadcast songs. In this study, we describe the acoustic features of a soft song in the brownish-flanked bush warbler Cettia fortipes. Compared with the broadcast song, the warbler's soft song was characterized by a lower minimum frequency and longer duration, and it had a higher proportion of rapid frequency modulation notes. Using playback experiments, some in combination with mounted spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
(98 reference statements)
0
29
0
Order By: Relevance
“…Additionally, playback experiments with mounted specimens have shown that soft song is a reliable aggressive signal in male-male conflict (Searcy and Beecher 2009;van Staaden et al 2011;Searcy et al 2014). In a previous study, we found that the relationship between soft song production and subsequent attack is significant in the Brownish-flanked Bush Warbler Cettia fortipes (Xia et al 2013b). Here, we examined the correlation between soft song production and subsequent attack in different male-male conflict contexts in this species.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Additionally, playback experiments with mounted specimens have shown that soft song is a reliable aggressive signal in male-male conflict (Searcy and Beecher 2009;van Staaden et al 2011;Searcy et al 2014). In a previous study, we found that the relationship between soft song production and subsequent attack is significant in the Brownish-flanked Bush Warbler Cettia fortipes (Xia et al 2013b). Here, we examined the correlation between soft song production and subsequent attack in different male-male conflict contexts in this species.…”
Section: Introductionmentioning
confidence: 61%
“…For signals with no obvious physiological or anatomical constraints, cost should be the most probable explanation for the stability of the signaling system (Vehrencamp 2000;Molles and Vehrencamp 2001). A previous study showed that soft song can induce male brownish-flanked bush warbler to spend significantly more time near the loudspeaker (Xia et al 2013b). We hypothesized that closeness is a cost to the signaler in the experiment detailed by Xia et al (2013b) based on the underlying logic that increasing closeness increases the possibility of attack.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations